Regioisomeric dipyrazolyl−anthracene luminophores: mechanochromic luminescence switch and mercury ion detection with 'turn-off' response. (January 2022) - Wang, Zhi-Feng; Tong, Jin; Guo, Jing; Shang, Ping; Yu, Yan-Min; Wang, Xia-Yan; Yu, Shu-Yan
Abstract: A series of regioisomeric luminophores L1 –L8 with 1 H -pyrazol-3-yl or 1 H -pyrazol-4-yl substituents at the different positions of anthracene core have been synthesised and characterised. According to the photophysical properties and related frontier orbital features of these compounds, the 'site-effect' of pyrazolyl substituent on an anthracene unit can be found, demonstrating the dependence of the properties of the compound on the position of substitution of the pyrazolyl moieties connecting to the anthracene core. Moreover, the target luminophores present reversible mechanochromism properties. The most significant mechanochromism luminescence is achieved for luminophores L1 and L2 with pyrazolyl substituents at the 9-and 10-positions of the anthracene unit. Upon grinding the pristine powder sample, a colour change from light yellow to yellow-green is observed. In addition, the target luminophores L2, L4, L6 and L8 demonstrate sensing properties of Hg 2+ ions with high selectivity and exceptional sensitivity. These findings suggest that these anthracene-centred luminophores are promising functional platforms with fluorescence and selective heavy metal sensor arrays. Graphical abstract: Image 1 Highlights: We designed and synthesized eight regioisomeric dipyrazolyl−anthracene luminophores. The new luminophores exhibit different behaviour in mechanochromism property as mechanochromic luminescence switch. The target luminophores demonstrate sensing properties of Hg 2+ ion with high selectivity and exceptional sensitivity.